2019
DOI: 10.1038/s41598-019-42191-0
|View full text |Cite
|
Sign up to set email alerts
|

Delayed maturation of GABAergic signaling in the Scn1a and Scn1b mouse models of Dravet Syndrome

Abstract: Dravet syndrome (DS) is a catastrophic developmental and epileptic encephalopathy characterized by severe, pharmacoresistant seizures and the highest risk of Sudden Unexpected Death in Epilepsy (SUDEP) of all epilepsy syndromes. Here, we investigated the time course of maturation of neuronal GABAergic signaling in the Scn1b −/− and Scn1a +/− mouse models of DS. We found that GABAergic signaling remains immature in both DS models, with a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 59 publications
(74 reference statements)
3
31
1
Order By: Relevance
“…6D, F, 9C and Table 2B). This small reduction may be attributed to impaired activity of inhibitory neurons, alteration in the reversal potential of chloride (Yuan et al, 2019), or both.…”
Section: Dsmentioning
confidence: 99%
“…6D, F, 9C and Table 2B). This small reduction may be attributed to impaired activity of inhibitory neurons, alteration in the reversal potential of chloride (Yuan et al, 2019), or both.…”
Section: Dsmentioning
confidence: 99%
“…The failure-to-thrive phenotype of Scn1b -/pups precluded the implantation of EEG electrodes. 28 Behavioral seizures were not observed in Scn1b Fl/Fl /Emx1-Cre or Scn1b Fl/Fl / Camk2a-Cre mice and all mice survived for more than 90 days. These data suggest a crucial role for PV + interneurons in Scn1b-linked seizures and SUDEP.…”
Section: Scn1b Deletion In Pv + Neurons Results In Seizures and Sudepmentioning
confidence: 92%
“…34 In other work, we reported that the time courses of maturation of neuronal GABAergic signaling in neocortical layer II/III and hippocampal CA1 or CA3 pyramidal cells are delayed in both the Scn1b −/− and Scn1a +/− mouse models of DEE, such that GABAergic signaling remains excitatory in these brain regions for significantly longer periods of development compared to WT. 28 This important point should be considered in the context of both DS and EIEE52 when discussing the effects of disinhibition, in that defects are not limited to impaired PV + neuron firing but also that inhibitory neurotransmission is further dampened by the impaired capacity of postsynaptic cells to receive these inputs as inhibitory. We found that the mean reversal potential for GABA in Scn1a +/− neurons was less depolarized than that of Scn1b −/− neurons over a similar developmental time range, again suggesting that these two DEE models exhibit ª 2020 The Authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 A delayed maturation of GABAergic signaling may contribute to epileptogenesis in this model. 30 Mice have a lower threshold for spreading depolarization, 31 and neurons derived from patients with Dravet syndrome show hyperexcitability, and cardiac myocytes show increased spontaneous contraction rates. 32,33 Abnormal sleep architecture but not total sleep duration probably due to an imbalance between excitatory and inhibitory neurons in the thalamocortical network.…”
Section: Animal Modelmentioning
confidence: 99%